The Multidimensional and Hierarchical Nature of the Questionnaire for Eudaimonic Wellbeing: A Bifactor-ESEM Representation in a Spanish Sample - Fadda, Daniela; Quevedo-Aguado, M. Paz; Benavente Cuesta, María H.; Scalas, L. Francesca (Frontiers in Psychology, 2020)
Aim of the present study is to support the multidimensional and hierarchical nature of the Spanish version of Questionnaire for Eudaimonic Wellbeing (QEWB) and to analyze its psychometric properties through the exploratory structural equation modeling (ESEM) framework. Results of the analyses carried out in a sample of university students (N = 589, 161 males and 428 females), supported the hypothesized bifactor-ESEM solution, composed by a global eudaimonic wellbeing factor and three specific factors (Sense of Purpose, Purposeful Personal Expressiveness and Effortful Engagement). Specifically, the global factor is relatively well defined by most of the 21 items; moreover, two of the specific factors (Purposeful Personal Expressiveness, Effortful Engagement) keep their own meaningful specificity apart from that explained by the global factor, suggesting that they add information to the eudaimonic wellbeing construct. Regarding criterion-related validity of the QEWB, the global factor was positively correlated with self-esteem. Finally, the scale showed adequate levels of composite reliability and measurement invariance over gender. Differences in latent means showed that girls report higher positive Purposeful Personal Expressiveness and Effortful Engagement than boys, whereas no significant differences were found in relation to global eudaimonic wellbeing. Theoretical implications about the nature of eudaimonic wellbeing are considered.